Investigation into the characteristics of silicon photovoltaic converters of solar batteries in case of overheating - Ivanchenko, A. V.; Mazuryk, S. V.; Tonkoshkur, A. S. (Technology and design in electronic equipment, 2018)
Recently, solar panels have become one of the most desirable sources of renewable electrical energy, and thus the requirements for their reliability, in particular to maintain the basic functional properties at elevated temperatures, are increasing. The basic element of solar batteries is photovoltaic converter. Until now, the degree of degradation and ways to protect photovoltaic converters during overheating corresponding to real situations during their exploitation, are not sufficiently studied.In this paper, the authors study one of the important problems arising during the development of circuit-technical devices for the protection of the photovoltaic converters against electrothermal overloads, namely, the problem of the effect of overheating of photovoltaic converters on their functional properties. Primarily, this is important in connection with the perspective of using functional electronics to improve the reliability of the photovoltaic system of the solar battery. In particular, resettable fuses based on polymeric nanocomposites with carbon fillers are such elements of the electronics. One of the difficulties of direct application of the resettable fuses is that they have a switching temperature that exceeds the standard operating temperature range of the modern photovoltaic converters.The paper presents investigations results of the current-voltage and volt-watt characteristics of the single-crystal silicon photovoltaic converters of the solar batteries, which have undergone heat treatment at elevated temperature (up to 150°C) at different time intervals (up to 6 hours) under lighting conditions and in dark mode in open- and short-circuited states.The method based on fixing the deviations of the functional parameters (i.e., open-circuit voltage, short-circuit current and maximum power) of the converters from their nominal values was used for their analysis.It has been established that in the investigated temperature and time ranges there are no significant changes of the main functional characteristics and parameters of the photovoltaic converters based on single-crystal silicon.